Model Pembelajaran Berbasis Masalah (PBL) Pada Mata Pelajaran Bahasa Jepang (Penelitian dan Pengembangan di Kelas IX SMAN 75 Jakarta) - Rita Agustina Karnawati (Vocational College of Diponegoro University, 2022)
In the 21st century, the role of education is becoming increasingly important in preparing the next generation who have the skills to learn and innovate, the skills to use technology and information media so that the learning model needed is an active, innovative, creative, effective. One of the learning models that are considered appropriate to meet that educational objectives is the use of problem based learning (PBL) learning models in classroom teaching.The purpose of this study was to determine the Japanese language skills of class XI students of SMAN 75 Jakarta and whether the learning model to be developed for Japanese subjects in class XI of SMAN 75 Jakarta was effective compared to the learning model carried out before the development. The research method is student-based learning with the research design being Pre-Experimental Design with the One-Group Pretest-Posttest Design model. The study included 39 students from SMAN 75 Jakarta's class XI. Data analysis in the study was carried out in several stages, namely the validity test, reliability test, normality test, and t test. The findings revealed that there was a difference after using problem-based learning model on Japanese language abilities acquisition when compared to before treatment. And the problem-based learning model is effective in developing Japanese language abilities.